(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This article describes the theory of the time-based frequency-locked loop (TFLL), intended for tracking the input signal periods, which change extremely rapidly. They are based on the processing of the input signal periods. The described algorithm, when appropriately implemented, can also be applied to track and predict any physical variable in real time, provided that the pulse signal period is replaced with periodic data from the physical variable. The paper presents a mathematical procedure for determining optimal system parameters for tracking rapidly changing periods. Since this mathematical procedure is very lengthy for higher-order systems, the paper focuses on a new abbreviated analysis method based on a tabular approach. This approach has not been described in the literature so far. Mathematical analyses in the time domain were performed using the Z transformation. Simulation of the system operation was carried out. For frequency-domain analysis, the theory of FIR digital filters and the corresponding MATLAB software were used. The system’s tracking capabilities are demonstrated in the time and frequency domains.